The crocodile who came for dinner - Smallman,Steve; Dreidemy, Joelle (London: Little Tiger, 2022)
Hotpot and Wolf have found an egg. A CROCODILE egg! Is the crocodile a fearsome, ferocious beast? No! He's snuggly, cuddly and looking for some friends.
Originally published: 2021.
Preschool.